Safety and Feasibility of Ultrasound-Guided Access for Coronary Interventions through Distal Left Radial Route - Tapan Ghose; Ranjan Kachru; Jaideep Dey; Wasi Ullah Khan; Ratna Sud; Suraiya Jabeen; Shahnawaz Husain; Aparna Pant (Journal of Interventional Cardiology)
Aims. Left distal transradial arterial approach (ldTRA) is a new interventional route that spares right radial artery (RRA) for use in haemodialysis and as bypass graft. Vasant Kunj Left dIstal Transradial ArtEry approach (VKLITE) study aimed to assess the feasibility and safety of ldTRA access during coronary angiography (CAG) and percutaneous coronary intervention (PCI). Methods and Results. Between April 2018 and June 2020, 108 patients were enrolled and underwent CAG ± PCI via ultrasound guided ldTRA. Arterial puncture, CAG, and PCI were successful in 96.3% (104/108), 92.1% (93/101), and 94.1% (32/34) patients, respectively. Access site crossover rate was 14/108 (13.0%). Mean puncture, procedure, and haemostasis time (minutes) were 6.7 ± 7.1, 55.7 ± 32.8, and 23.1 ± 11.9. Median total fluoroscopic time was 6.6 minutes (IQR-14.2), and median total radiation dose was 39.2 Gy-cm2 (IQR-97.0). Local haematoma occurred in 11 patients (10.2%) with major haematoma in 1.9%, all recovering within three weeks. Mean pain score was 2.4 ± 2.3, and patient satisfaction score was 9.0 ± 1.3. LdTRA access compared with RRA access (n = 121) showed significantly increased mean procedure time (55.7 ± 32.8 vs. 43.9 ± 26.0 minutes, p = 0.01) and median total fluoroscopic time (6.6 [IQR-14.2] vs. 4.7 [IQR-8.2] minutes, p = 0.02), with similar median total radiation dose (39.2 [IQR-97.0] vs. 43.8 [IQR-54.5] Gy-cm2, p = 0.56). No radial artery loss, dissection, pseudoaneurysm, arteriovenous fistula, or nerve injury was noted. Conclusions. LdTRA access is feasible with few complications during CAG/PCI. Patient comfort and satisfaction makes it a desirable route for coronary interventions.